Ruptured Ectopic Pregnancy Misdiagnosed with Ruptured Corpus Luteum: A Case Report and Literature Review - Wing Yu Sharon Siu; Dah-Ching Ding (Gynecology and Minimally Invasive Therapy)
Ectopic pregnancy can be mistakenly reported as a ruptured corpus luteum. A 22-year-old woman was initially misdiagnosed with a ruptured corpus luteum and treated with analgesics at a local clinic. Persistent symptoms led her to our hospital, where a pelvic ultrasound revealed a 5.2 cm ×4.8 cm hematoma. Despite the significant hematoma, her vital signs were stable. A urine pregnancy test was positive, β-hCG was 5553 mIU/mL, and hemoglobin (Hb) was 6.3 g/dL. After a blood transfusion, methotrexate (MTX) was administered, reducing β-hCG to 4428 mIU/mL by day 5. Four weeks later, β-hCG was 723.6 mIU/mL, and a second MTX dose was given. Three weeks later, β-hCG was 4.7 mIU/mL, and Hb was 12.4 g/dL. In conclusion, a “wait-and-see” approach with serial hCG testing and repeated ultrasounds is recommended in unclear cases.